2012
DOI: 10.1162/jocn_a_00174
|View full text |Cite
|
Sign up to set email alerts
|

Stress Sensitizes the Brain: Increased Processing of Unpleasant Pictures after Exposure to Acute Stress

Abstract: A key component of acute stress is a surge in vigilance that enables a prioritized processing of highly salient information to promote the organism's survival. In this study, we investigated the neural effects of acute stress on emotional picture processing. ERPs were measured during a deep encoding task, in which 40 male participants categorized 50 unpleasant and 50 neutral pictures according to arousal and valence. Before picture encoding, participants were subjected either to the Socially Evaluated Cold Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 42 publications
8
44
1
1
Order By: Relevance
“…To control for group differences during encoding, free recall procedures (e.g., Wichert et al, 2013a) and explicit learning tasks with performance control after learning (e.g., Hupbach et al, 2007) were used in previous studies. In order to rule out possible group differences during encoding in the present study we analyzed the late positive potential (LPP) as measure of attention processing that has also been associated with memory performance (Weymar, Schwabe, Löw, & Hamm, 2012). However, we found larger LPPs in response to emotional pictures compared to neutral ones replicating many previous studies (e.g., Cuthbert, Schupp, Bradley, Birbaumer, & Lang, 2000;Schupp et al, 2004), but no group differences.…”
Section: Discussionsupporting
confidence: 80%
“…To control for group differences during encoding, free recall procedures (e.g., Wichert et al, 2013a) and explicit learning tasks with performance control after learning (e.g., Hupbach et al, 2007) were used in previous studies. In order to rule out possible group differences during encoding in the present study we analyzed the late positive potential (LPP) as measure of attention processing that has also been associated with memory performance (Weymar, Schwabe, Löw, & Hamm, 2012). However, we found larger LPPs in response to emotional pictures compared to neutral ones replicating many previous studies (e.g., Cuthbert, Schupp, Bradley, Birbaumer, & Lang, 2000;Schupp et al, 2004), but no group differences.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, converging evidence from multiple elegant readout measurements in the present study as well as our previous studies, including increase in hear rate and cortisol, changes in pupil dilation responses (Henckens et al, 2009; Qin et al, 2012) and increase in α-amylase and amygdala perfusion (Cousijn et al, 2010, 2012), firmly promote the conclusion that our emotion focused stress induction procedure was effective. That is, our procedure indeed successfully induced a state characterized by hyperactivation of catecholaminergic systems and negative mood (Arnsten and Goldman-Rakic, 1998; Arnsten, 2009; Hermans et al, 2011; Shackman et al, 2011; Weymar et al, 2011). …”
Section: Discussionmentioning
confidence: 82%
“…During hand immersion, participants were videotaped, asked to look straight into the camera and told that video recordings would later be analyzed for facial expressions. Several studies have shown that the SECPT is an effective stress induction method that leads to significant elevations in autonomic arousal, salivary cortisol and subjective stress ratings [34][36]. Participants in the control condition (N = 26) immersed their right hand including the wrist for 3 min in warm water (35–37°C).…”
Section: Methodsmentioning
confidence: 99%